Optimization of the Brewing of “Kablé-Missine”, Togo Northern Local Sorghum Beer (International Journal of Scientific Research and Management (IJSRM), 2024)
Kablé-missine is a traditional alcoholic beverage predominantly brewed in Northern region of Togo. Despite its widespread consumption and use in various festivities, its quality varies enormously depending on the individual brewing methods. This study aimed to optimize the brewing process of local sorghum beer, kablé-missine, with a particular focus on malting and mashing. Local sorghum grains were subjected to steeping, and key parameters including moisture content during malting, pH, and Brix of the wort were evaluated. The moisture content significantly increased during the steeping phase (39.77 ± 0.44%) and subsequently decreased during germination (37.93 ± 0.53%). The pH of the acidification process was adjusted to 3.11 ± 0.02, and the Brix level significantly increased with extended boiling time in both samples. Moreover, using a limited amount of water during mashing effectively reduced the boiling time.